TINGKAT STRES PADA LANSIA DENGAN STATUS JANDADI DESA KALIJAJAR WETAN PAITON PROBOLINGGO - Ma’rifah, Asirotul; Zahro, Fatimatus (JURNAL KEPERAWATAN SEHAT, 2016)
Phenomena that occur in the village of Kalijajar elderly who lost a lot of Weta partnerespecially in elderly women many of them widows and they look gloomy, uneasy andnot excited in the daily activities of living. Research objectives, namely the level of stress on the elderly with the status of a widow. The design of this research is descriptive. The entire research population are elderly widows in the village of Kalijajar Wetan Paiton Probolinggo as many as 32 respondents. The samples were taken with the total sampling techniques. Variables in this research,are level of stress experienced by the elderly with the status of a widow. Data taken with the instruments and questionnaires were processed by means of editing, coding, scoring and the tabulating later presented in the form of a frequency distribution table. The results showed of the 32 respondents most had levels of stress in the category are currently as many as 19 respondents (59,4%). This happens because the respondents still have not been able to adapt to the circumstances that happened to them when they have the status of a widow, so that respondents feel confused and worried. So that the respondents may be expected to increase understanding in the treatment of stress and can detect any stressor early so that respondents can indicate an Adaptive koping mechanism in the face of stress being experienced.